Assessing coastal ecosystem carrying capacity by a comprehensive economy-resources-environment system: A case study of South Korea. (1st August 2022) - Wang, Chaoyi; He, Xiaolong; Ma, Mengyue; Xiong, Liuhuizi; Zhang, Weiwei
Abstract: Ocean warming, acidification, oxygen loss, marine pollution, overfishing, and habitat destruction have put significant stress on both ocean health and coastal ecosystems. However, as coastal ecosystem carrying capacity (ESCC) is vital to sustainable coastal ecosystem development and societal and environmental well-being, to engender a more harmonious human-ocean coexistence, this paper developed a comprehensive coastal ESCC evaluation index system based on economic development, resource utilization, and environmental governance, which was then employed to analyze South Korea's coastal ESCC from 2009 to 2019. It was found that South Korea's coastal ESCC slightly improved over the 11-year study period, although there were fluctuations. There was a decrease in coastal ESCC health in 2014 because of the Sewol ferry event and in 2019 because of the Hanjin Shipping bankruptcy and the impact of the 2018 Terminal High Altitude Area Defense deployment. Based on the findings, several policy development suggestions are given.